You've got dissent! : Chinese dissident use of the Internet and Beijing's counter-strategies - Chase, Michael (RAND, National Security Research Division Center for Asia Pacific Policy, 2002)
An analysis of the political use of the Internet by Chinese dissidents, both in the PRC and abroad, and the counterstrategies that Beijing has employed to prevent or minimize its impact. Although PRC officials have responded to the increased use of the Internet with predominantly traditional measures, they have been relatively successful. No credible challenges to the regime exist at present, despite the introduction of a massive modern telecommunications infrastructure. However, time may be on the side of the regime's opponents.